Talent Retention and Turnover: Diagnosis and Discussion of Factors from a Case Study - Souza, Pâmela Luciana (2022)
This study aimed to carry out a situational diagnosis about the employee turnover of a large company, located in the city of Campinas - SP. In addition to the theoretical part, the research sought to contribute with the selected company in the initial efforts to identify causes of voluntary turnover and determinants for talent retention. Data collection was carried out through the application of questionnaires by electronic way, in a target audience formed by 20 managers and 40 employees. The data revealed a mismatch between the situational understanding of employees and managers in several points that were highlighted as relevant for the permanence of employees, such as the career plan and the relationship with the managers. The case study showed, similar to what is found in the literature, how the insufficiency of concrete talent retention management measures by the company ends up resulting, for example, in the high turnover faced. Theoretically, this study reinforces the need for the evolution of human resources management models in the generational pace and in the multiple individual and social needs.